1
$\begingroup$

I have a few questions regarding powers.

We have:

\begin{align} (x\cdot y)^n &= x^n\cdot y^n \tag 1\\ (x^m)^n &= x^{m\cdot n} \tag 2\\ x^m \cdot x^n &= x^{m+n} \tag 3 \end{align}

Question 1:

I guess a special case of $(1)$ is $y=x$, so: \begin{align} (x\cdot x)^n \underbrace{=}_\text{$(1)$} x^n\cdot x^n \underbrace{=}_\text{$(3)$} x^{n+n} =x^{2n} \tag 4 \end{align} Is this correct?

Question 2:

If a special case of $(3)$ is $m=n$ we have: $$ x^n\cdot x^n \underbrace{=}_\text{$(3)$} x^{n+n}=x^{2n} \tag 5 $$

Is this correct?

But if $m=n$ in $(2)$ we have: $$(x^n)^n \underbrace{=}_\text{$(2)$} x^{n\cdot n} = x^{n^2} \tag 6 $$

And this doesn't make sense... I guess it contradicts $(4)$ and $(5)$?

Thanks in advance!

$\endgroup$
  • 4
    $\begingroup$ Why does the last one not make sense? $\endgroup$ – blub Apr 3 at 9:34
  • 1
    $\begingroup$ Everything seems in order for me ... $\endgroup$ – Matti P. Apr 3 at 9:35
  • $\begingroup$ Hi! I updated the question. I think $(6)$ contradicts $(4)$ and $(5)$? $\endgroup$ – Joyat Apr 3 at 9:37
  • 1
    $\begingroup$ I think you accidently assume $(x^n)^n = x^n \cdot x^n$ which is of course not corret. $\endgroup$ – The Pheromone Kid Apr 3 at 9:38
  • 1
    $\begingroup$ You are probably thinking that $(x^{n})^{n}=x^{n}x^{n}$. That is not true. There is no contradiction in 4) ,5) and 6). $\endgroup$ – Kabo Murphy Apr 3 at 9:39
0
$\begingroup$

I think your confusion may be the fact that you think you calculate the same expression three times, but in the first two cases you compute $\color{blue}{x^n \cdot x^n}$ in two ways (or using two properties) while in the last case, you compute $\color{purple}{(x^n)^n}$ and that's not the same: $$\underbrace{\color{blue}{x^n \cdot x^n}}_{2\text{ factors}} = (x^n)^2 \color{red}{\;\mathbf{\ne}\;} \color{purple}{(x^n)^n} = \underbrace{x^n \cdot x^n\cdot \ldots\cdot x^n}_{n\text{ factors}} $$

$\endgroup$
0
$\begingroup$

From the looks of it, you expected $x^n\cdot x^n$ and $(x^n)^n$ to be the same, somehow?

Well, they are not. If we expand the exponents into repeated products of $x$ (this is assuming $n$ is a natrural number), we see that $$ x^n\cdot x^n = \underbrace{x\cdot x\cdots x}_{n\text{ times}}\cdot \underbrace{x\cdot x\cdots x}_{n\text{ times}} $$ for a total of $2n$ $x$'s, while $$ (x^n)^n = (\underbrace{x\cdot x\cdots x}_{n\text{ times}})^n\\ = \underbrace{\underbrace{x\cdot x\cdots x}_{n\text{ times}}\cdot \underbrace{x\cdot x\cdots x}_{n\text{ times}}\cdots\underbrace{x\cdot x\cdots x}_{n\text{ times}}}_{n\text{ times}} $$ for a total of $n\cdot n$ $x$'s.

Of course, if $n = 2$, or $n = 0$, or $x = 1$ or $x = 0$, then they happen to be the same. But in general they are quite different.

$\endgroup$
0
$\begingroup$

Question 1

This is indeed correct. In fact, another way to see it is to work from your equation (2): $$ (x \cdot x)^n = (x^2)^n \underbrace{=}_{(2)} x^{2n} $$

Question 2

This is also correct.

Question 3

Why does this not make sense? Consider a simple example with $x=2, m=2, n=3$. Equation (2) provides $$(x^m)^n = x^{mn} = 2^{2 \cdot 3} = 2^6 = 64$$ If we work it out without using the identity, we obtain $$(x^m)^n = (2^2)^3 = 4^3 = 64$$ which is the same. If you think the identity does not make sense, then what would your expected result be? Try an example and see if it is correct.

I hope this helps!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.